2013
DOI: 10.1002/fuce.201300026
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Gd‐CeO2 Electrolyte for SOFC Prepared by Aqueous Tape Casting

Abstract: Mechanical properties of gadolinium‐doped ceria (Ce0.9Gd0.1O1.95, 10GDC) green tape prepared by aqueous‐based tape casting process were characterized by tensile test and shear punch test (SPT). SPT was found to be a useful method for characterizing mechanical properties of green tapes. Microstructures and mechanical properties such as flexural modulus, bending strength, and microhardness of tapes sintered at 1,300–1,500 °C have been evaluated. Indentation fracture toughness was also determined by the method of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…All doped ceria samples showed higher hardness than pure ceria, which is in agreement with the reported results in literature [29]. EDC sample demonstrated the highest hardness that could be related to improving the atomic bonds by doping ceria with Er as it was seen in elastic modulus measurement earlier and YDC samples has the lowest hardness among doped ceria samples, which could attributed to lower density due to having high porosity [15,19].…”
Section: +supporting
confidence: 90%
See 1 more Smart Citation
“…All doped ceria samples showed higher hardness than pure ceria, which is in agreement with the reported results in literature [29]. EDC sample demonstrated the highest hardness that could be related to improving the atomic bonds by doping ceria with Er as it was seen in elastic modulus measurement earlier and YDC samples has the lowest hardness among doped ceria samples, which could attributed to lower density due to having high porosity [15,19].…”
Section: +supporting
confidence: 90%
“…There are more reports for mechanical properties of ceria doped with gadolinium and samarium [15][16][17][18][19] [17,21,22]. The assynthesized powders were calcined at 700°C for 2h.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the crack length is greater than 2 times of indentation size ( c > 2a) as shown in Figure , which satisfies the requirement of equation . Akbari‐Fakhrabadi have measured the fracture toughness of pure GDC sintered at 1500°C using the indentation method and reported their data of 1.35 ± 0.51 MPa·m 1/2 . The fracture toughness data for SNDC/LSO composites are demonstrated in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Akbari-Fakhrabadi have measured the fracture toughness of pure GDC sintered at 1500°C using the indentation method and reported their data of 1.35 AE 0.51 MPaÁm 1/2 . 38 The fracture toughness data for SNDC/LSO composites are demonstrated in Figure 5. It can be seen that the fracture toughness increases initially with the addition of LSO and shows a maximum at the content of 5%.…”
Section: Resultsmentioning
confidence: 99%
“…The hardness of the ferrites was measured using a Vickers hardness tester (Akashi MVK-H1) on the polished surface of the sintered samples, with a load of 1 kg for 10 s to create cracks with a suitable shape under indentation, with a minimum of 10 indentations per sample [26]. The flexural strength (σ C ) at room temperature was determined, according to a standard three-point method for bending strength testing (ASTMC674), by means of a computerassisted Cometech QC-506A2 Universal testing machine [27]. ceramics was seriously inhibited at an SnO 2 content of Z3.5 wt%, and the maximum sintered density of $ 5.26 g/cm 3 was obtained at a sintering temperature greater than 1150 1C, as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%